Meningkatkan Literasi dan Numerasi Serta Mengajarkan Untuk Menyebar Hal Hal Positif - Muhammad Aimar Zaiddan; Hairani Siregar (Yayasan Literasi Sains Indonesia, 2023)
Education is the learning of knowledge, skills and habits of a group of people passed down from one generation to the next through teaching, training or research. The development of education in Indonesia has indeed gone through a very long way. From time to time there is a transformation of education so that the direction of education in Indonesia is even better. Education transformation in Indonesia usually begins with the curriculum used, teacher teaching techniques, how to access lessons and so on. You could say that education in Indonesia is now better, especially with the presence of increasingly sophisticated technology. One of the educational programs in Indonesia is the teaching campus. Campus teaching is a program where students can practice their knowledge in a designated school. The teaching campus itself has been implemented in various public and private campuses in Indonesia. North Sumatra University is one of the universities that organizes teaching campuses. However, the University of North Sumatra has introduced its own version of the teaching campus concept, which is referred to as USU's partner teaching campus. The aim of this program is to improve the quality of education in the province of North Sumatra. And students of the Social Welfare Study Program can run USU's partner teaching campus programs while carrying out field work practices.